Consumer Intention to Adopt Dockless Bike Sharing Scheme in Southern China Based on Value-Attitude- Behavior Model - Zhu, Bing (Animo Repository, 2021)
This study aims to reveal the influences of personal value priorities on consumers’ environmental attitude and their intention to adopt fourth-generation shared bikes (DBSS) in Southern China based on the value-attitude-behavior model. Also, how environmental attitude mediates the relationship between predictors and consumer intention to adopt DBSS is tested. Three hundred sixty-three self-administrated questionnaires were collected in Nanning City in China. Quota sampling, judgmental sampling, and convenient sampling techniques were applied for data collection. In terms of data analysis, the partial least square structural equation model (PLS-SEM) approach based on Smart PLS 3 was employed to evaluate the structural equation model and mediation effect. The results reveal that openness-to-change plays the most important role in affecting consumer environmental attitude, which significantly influences consumers’ intention to adopt a dockless bike- sharing scheme. Also, the mediation effect of environmental attitude is confirmed. Thus, it is recommended that certain programs be organized to boost the usage of DBSS and create a good public reputation for the users and companies, and creating an inclusive environment at the firm level is necessary to facilitate the user community.